Hubungan antara Hipertensi, Merokok dan Minuman Suplemen Energi dan Kejadian Penyakit Ginjal Kronik - Titiek Hidayati, Haripurnomo Kushadiwijaya, Suhardi (Berita Kedokteran Masyarakat (BKM), 2008)
Background: Chronic kidney diseases (CKD) are a global health problem with increasing incidence, prevalence and mortality rate. So far no study has been known to have been conducted on factors related to the prevalence of renal failure disease in Yogyakarta.Objective: The study was aimed to identify relationship between hypertension, smoking and supplement energy drink and CKD at PKU Muhammadiyah Hospital Yogyakarta and calculate odds ratio of these factors.Method: The study was analytical observation with case control design. There were as many as 210 subjects divided into three groups. The first group consisted of 70 patients of terminal chronic renal failure who had routine hemodialysis treatment at PKU Muhammadiyah Hospital Yogyakarta as cases. Diagnostic criteria of CKD were specified through serum creatinin level > 10mg/dl and the requirement for routine hymodialysis. The second group consisted of 70 patients of conscious trauma victims or hemorrhagic fever or typhoid fever infection with creatinin level < 1.37 mg/dl living close to the residence of the cases hospitalized at PKU Muhammadiyah Hospital as hospital controls. The third group consisted of 70 healthy volunteers with the same sex, age, ethnic group and residency with cases that had creatinin level < 1.37mg/dl as community controls. Inclusion criteria for the subject were Indonesian of 15 – 65 years old, willing to participate in the study by filling in and signing letters of agreement and informed consent. Exclusion criteria were: heredity chronic disease and renal transplant history. Secondary data were obtained from patients’ medical records. Primary data were obtained through in-depth interview guided by questionnaire for healthy volunteers, hospital cases and controls. Data analysis was carried out using univariable, bivariable, stratified and double logistic regression techniques. The results were presented through  tables, graphs or diagrams.Result: Hypertension, smoking and having supplement energy drink were risk factors of the prevalence of CKD at PKU Muhammadiyah Hospital, Yogyakarta. There was a dose-dependence on amount and length of smoking, supplement drink and time length of hypertension and the prevalence of CKD.Conclusion: Smoking, having supplement drink and hypertension have relationships with the prevalence of CKD at PKU Muhammadiyah Hospital, Yogyakarta. Odds ratio of smoking, having supplement drink and hypertension against the prevalence of terminal chronic renal failure at PKU Muhammadiyah Yogyakarta were perspectively 3.68(CI=1.39 – 9.74; p<0.05), 6.63 (CI=2.53 – 17.35; p<0.05) and 23.15 (CI=8.73 – 61.41; p<0.05).Keywords: chronic renal failure, risk factors, hypertension, energy drink, smoking